Mobile Aplikasi Scanning Parkir Pada Kendaraan Roda Dua (Study Kasus: SMPN 10 Bandar Lampung) - Rionaldi Ali; Yuni Puspitasari; Ari Yudha Sagita (TEKNIKA, 2022)
The case of vehicle theft until now has not been handled satisfactorily by the police. The best solution is to keep the vehicle by the owner himself, including the management of the parking lot, which is the main factor to reduce the number of vehicle losses. Template Matching is a technique in digital image processing to find the smallest parts that match the image with the image template as a reference. Templates in the context of pattern recognition refer to internal constructs that, if matched with a sensory stimulus, lead to the recognition of an object. To be able to work template matching requires two main components, namely: Image source is an image where we hope to find a match with the template image. A template image is an image that is used as a template or reference to be compared with the image source. The results are expected to minimize the occurrence of motorcycle theft cases again in schools or anywhere where the area is prone to theft. Based on the discussion of writing a thesis report on the design of a parking scan application, conclusions can be drawn, namely: The system facilitates the security guard whose job is to determine the compatibility of motorcyclists entering and leaving with the help of this program. The development of the vehicle parking scan application starts from the data collection method and is developed using the UCD method and also Template Matching.